PARP Inhibition and Beyond in BRCA-Associated Breast Cancer in Women: A State-Of-The-Art Summary of Preclinical Research on Risk Reduction and Clinical Benefits - Pauwels, Ernest K.J.; Bourguignon, Michel H. (Medical principles and practice, 2022)
In mammalian cells, DNA damage response initiates repair by error-free homologous recombination (HRR) or by error-prone non-homologous end joining (NHEJ). DNA damage is detected by PARP proteins that facilitate this repair, both in normal cells and in cancer cells. Cells containing BRCA1/2 mutations have an HRR-deficient repair mechanism which may result in unrepaired one-ended double-strand breaks and stalled replication forks, considered as the most lethal cell damage. Here, we review the state of the art of the role of Poly (ADP-ribose) polymerase (PARP) inhibitors as a precision-targeted anticancer drug in BRCA1/2-mutated female breast cancer. Although knowledge is incomplete, it is assumed that the main role of the archetype PARP1 in the cell nucleus is to detect and adhere to single-strand breaks. This mediates possible damage repair, after which cells may continue replication; this process is called synthetic lethality. As for PARP clinical monotherapy, progression-free survival has been observed using the FDA- and EMA-approved drugs olaparib and talazoparib. In the case of combined drug therapy, a synergy has been demonstrated between veliparib and platinum drugs. Information regarding adverse effects is limited, but hematological effects have been described. However, there is need for multicenter trials, preferably conducted without commercial guidance and funding. Some of the available trials reported resistance to PARP inhibitors. In this review, we also describe the various causes of resistance to PARP inhibitors and research indicating how resistance can be overcome.